Synthesis and Biological Activity of New 4-(Pyridin-4-yl)-(3-methoxy-5-methylphenyl)-1H-pyrazoles Derivatives as ROS Receptor Tyrosine Kinase Inhibitors - Park, Byung Sun; El-Deeb, Ibrahim M.; Yoo, Kyung Ho; Han, Dong Keun; Tae, Jin Sung; Lee, So Ha (WILEY-V C H VERLAG GMBH, 2012)
A series of new 4-(pyridin-4-yl)-(3-methoxy-5-methylphenyl)-1H-pyrazoles (6a-k & 7a-l) has been rationally designed based on the structure of the lead compound KIST301080, a selective ROS receptor tyrosine kinase inhibitor, in order to study the activity of ROS of this new class of inhibitors. The compounds were synthesized and screened against ROS kinase, where compound 6h showed moderate inhibitory activity with an IC50 value of 6.25 mu M. The study emphasized the importance of the acetonitrile group at the pyrazole ring and also the importance of having a hydrogen bond donor on the distal phenyl ring linked to the pyridine moiety.